Recovery of Conduction Following High-Power Short-Duration Ablation in Patients With Atrial Fibrillation: A Single-Center Experience. (29th September 2021) - Mohanty, Sanghamitra; Trivedi, Chintan; Della Rocca, Domenico G.; Gianni, Carola; MacDonald, Bryan; Quintero Mayedo, Angel; Al-Ahmad, Amin; Burkhardt, John D.; Bassiouny, Mohamed; Gallinghouse, G. Joseph; Horton, Rodney; Di Biase, Luigi; et al.
Abstract : Background: Optimal duration of energy delivery in high-power short-duration (HPSD) ablation to create a durable lesion in atrial fibrillation (AF) is not clear yet. We evaluated the association of electrical reconnection with lesion duration in HPSD-ablation. Methods: HPSD ablation was defined as maximum temperature at 42 °C and power delivery at 45 W for 10 to 15 seconds (5 seconds in coronary sinus [CS] and left atrial posterior wall [LAPW] near the esophagus). In some patients, a mechanical tool was used to deflect the esophagus away from the ablation site. Results: Consecutive 1749 patients with AF (left atrial appendage and CS isolation: 1451) receiving redo ablation after a prior HPSD procedure were included. At the HPSD ablation, mean duration of lesion was significantly shorter in the LAPW facing esophagus compared with elsewhere (5.2±1.5 versus 12.5±1.7 seconds, P <0.001). Application duration was reduced to <10 seconds in 1221 (84%) patients receiving left atrial appendage and CS isolation. At the redo, recovery of conduction was noted in the CS (592, 40.8%), left atrial appendage (493, 34%), and PV and LAPW (249, 14.2%). Of the 249 patients with LAPW reconnection, 91% (n=227) had the conduction recovered in the area facing the esophagus. In 73 patients, esophageal displacement device was used during the HPSD ablation. Average duration of lesions in LAPW among those 73 patients was 9.2±2 seconds. PV-LAPW reconnection was observed in 3/73 (4.1%) patients. Conclusions: HPSD ablation with lesion duration of <10 seconds was associated with conduction recovery in the left atrial appendage, CS, and the LAPW area facing esophagus.